Constipation and defecation disorders - Rao, Satish S. C. (Henry Stewart Talks, 2011)
Disorders of pelvic floor dysfunction such as constipation, solitary rectal ulcer syndrome and rectocle are very common and cause significant bowel symptoms and problems, Common presentations, underlying mechanisms and diagnostic modalities, Common approaches for treatment including biofeedback therapy